QUANTIFICAÇÃO DE METAIS EM PEIXES (GEOPHAGUS BRASILIENSIS, CYPRINUS CARPIO), ÁGUA E SEDIMENTO DO RESERVATÓRIO DE ALAGADOS EM PONTA GROSSA/PR E AVALIAÇÃO DA BIOCONCENTRAÇÃO E BIOACUMULAÇÃO - Voigt, Carmen Lúcia (2015)
From the concentration in water and sediment, bioconcentration and bioaccumulation of Ag, Al, As, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn were determined in gills, liver and muscles of Geophagus brasiliensis and gills and liver of Cyprinus carpio in the Alagados Reservoir, Ponta Grossa, Paraná, Brazil. Metals were quantified through atomic absorption spectrometry (AAS) and a study was carried out on the existing relations between metal and body weight, size and genre of this species. The level of metals in the waters of the reservoir was lower than the maximum levels allowed by legislation, except for that of Cd and Fe. In sediments, Cu, Cd, Cr and Ni presented concentrations above the threshold effect level adverse biological community and none of the analyzed metals exceeded the levels of probable effects level adverse. High concentrations of bioavailable metals were found in the sediment. In G. brasiliensis, Pb and Cr exceeded the limits stipulated in legislation for human consumption of fish. The metals Cu, Pb, Ag, As, Cd, Co and Ni had higher average concentrations in the liver and Fe, Mn and Zn had higher average concentrations in the gills G. brasiliensis. Statistical analysis did not showed significant differences in levels of metal concentration between body weight, size and gender of G. brasiliensis and the three analyzed tissues. The liver G. brasiliensis has higher affinity for that muscle bioconcentration and higher affinity for bioconcentration Cu, Co, Cd, Cr, Ni and Ag than the gills, that had the greatest affinity for bioconcentration Mn, Zn and Fe. How much bioaccumulation of metals in G. brasiliensis, the liver has greater affinity for metals muscle bioaccumulation and higher affinity for bioaccumulation Cu, Co, Cd, Cr, Ag, Pb, Ni and As than the gills. Bioconcentration and bioaccumulation of metals in G. brasiliensis tissues followed the global trend of Liver > Gills > Muscle. In C. carpio, the metals Mn, Zn, Co, Cd, Cr and Al had higher average concentrations in the gills and the metals Cu and Fe had higher average concentrations in the liver. The Pearson correlation showed that some metals significantly increase with the increase in the weight and size of C. carpio specimens, these being Al, Cr, Ni (P < 0,01), Cu, Fe (P < 0,05). Statistical analysis indicated that no significant differences in levels of metal concentration between gender C. carpio and the two analyzed tissues. The liver of C. carpio has more affinity for bioconcentration of Cu, Zn and Fe than the gills which have higher affinity for bioconcentration of metals Mn, Co, Cd, Cr, Ag and Ni. For bioaccumulation in C. carpio the liver has more affinity for bioaccumulation of Cu, Ag, Ni and Fe than the gills which have higher affinity for bioaccumulation Mn, Zn, Co, Cd, Cr, Pb and Al. In general, higher concentrations of metals occurred in the larger C. carpio specimens analyzed. The Alagados Reservoir has metal contamination and Geophagus brasiliensis and Cyprinus carpio species can be used as bio-indicators of environmental contamination.